2012
DOI: 10.9775/kvfd.2011.5623
|View full text |Cite
|
Sign up to set email alerts
|

Excision Arthroplasty of the Hip Joint in Dogs: The Role of Age, Weight, Degenerative Joint Disease on the Outcome

Abstract: The present clinical study was to evaluate the relationship between weight, degenerative joint disease (DJD) and age on the outcome in dogs underwent excision arthroplasty operation. 105 dogs have been referred to clinic with lameness on hindlimb. Dogs were younger than 1 year (50 dogs), 1 to 5 years (24) and older than 5 years (31). The rest of them were less than 10kg and the rest were heavier than 10kg. Lameness during walking was scored between zero to 5. Radiographic findings were showed that degenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…One theory is also that a larger dog has more excessive bone remodelling, bone-on-bone contact between the femoral neck and acetabulum, and bone lysis, which is thought to cause excessive pain and lameness [33]. However, there are studies that indicate that the weight of dogs could be of lesser importance to the outcome than commonly assumed [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…One theory is also that a larger dog has more excessive bone remodelling, bone-on-bone contact between the femoral neck and acetabulum, and bone lysis, which is thought to cause excessive pain and lameness [33]. However, there are studies that indicate that the weight of dogs could be of lesser importance to the outcome than commonly assumed [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Possible complications of this technique are hemorrhage, sciatic nerve damage, pin loosening, pin track drainage and disruption of the flexible band [9,31] . Additionally, total hip replacement [22][23][24] and femoral head and neck osteotomy [2,25,26] can be also BELGE, BOZKAN, SARIERLER, YAYGINGÜL applied for the treatment of hip luxation, however these techniques are usually preferred, if there is degenerative joint disease. In a multicenter internet based study on assessment of canine total hip replacement in 170 dogs, there were only 6 dogs which applied total hip replacement with coxofemoral luxation treatment indication [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study on femoral head and neck osteotomy, it was indicated that weight is not as much effective as age on the outcome, when the dogs were grouped as under and above 10 kg body weight [26] . However, according to some sources, femoral head and neck osteotomy require the dog below 17 kg [1] or 22 kg [37] body weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple pelvic osteotomy is frequently used for the treatment of hip dysplasia in immature dogs. The ideal candidates for triple pelvic osteotomy should have minimal to no degenerative osteoarthritis seen on radiographs and positive Ortolani sign 8,10 . The primary objective of this surgery is to improve joint stability by rotating the dorsal rim of the acetabulum laterally, thus providing greater dorsal coverage of the head.…”
Section: Introductionmentioning
confidence: 99%